2016
DOI: 10.1080/0142159x.2016.1231914
|View full text |Cite
|
Sign up to set email alerts
|

The impact of socially-accountable health professional education: A systematic review of the literature

Abstract: This literature review describes the impact of health professional schools with a social accountability mandate by identifying characteristics of medical education found to impact positively on medical students, health workforce, and health outcomes of disadvantaged communities. A critical appraisal tool was used to identify the strengths and weaknesses of the published articles. Data are presented as a narrative synthesis due to the variety of methodologies in the studies, and characterized using a logic mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
86
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(97 citation statements)
references
References 38 publications
2
86
0
9
Order By: Relevance
“…The experienced inequalities in health and well‐being may be countered by the basic concept of caring and showing respect in individual meetings (Nelson et al, ). An example of initiatives toward this end are the socially accountable health professional education (SAHPE) schools created worldwide to achieve health equity, through transforming healthcare professional education to meet local needs (Preston, Larkins, Taylor, & Judd, ; Reeve et al, ). This entails working in partnership with communities to provide health services that meet community needs, and to undertake research that is responsive to community priorities.…”
Section: Discussionmentioning
confidence: 99%
“…The experienced inequalities in health and well‐being may be countered by the basic concept of caring and showing respect in individual meetings (Nelson et al, ). An example of initiatives toward this end are the socially accountable health professional education (SAHPE) schools created worldwide to achieve health equity, through transforming healthcare professional education to meet local needs (Preston, Larkins, Taylor, & Judd, ; Reeve et al, ). This entails working in partnership with communities to provide health services that meet community needs, and to undertake research that is responsive to community priorities.…”
Section: Discussionmentioning
confidence: 99%
“…The medical school at Walter Sisulu University in South Africa has made a significant contribution to the collaboration on equitable selection methods. The two schools in the Philippines, Ateneo de Zamboanga University School of Medicine and the University of the Philippines Manila School of Health Science, Palo, have produced very high levels of graduate retention in a country where many health professional and medical graduates seek employment overseas …”
Section: The Local In Medical Education: Social Accountabilitymentioning
confidence: 99%
“…However, the Commission reports that this has not been a priority for medical schools and that there is a weak culture of ongoing monitoring and longer‐term outcome evaluation. Further, in a systemic review of the literature on the impact of socially accountable health professional education, Reeve et al found that there were few studies of the impact of socially accountable health professional education programmes on communities and health outcomes . There is much work to be done by medical schools on the impact of their educational programmes and the impact of their students on the health systems that employ them.…”
Section: The Global–local Tension In Medical Education: a Research Agmentioning
confidence: 99%
See 1 more Smart Citation
“…The Eastern Visayas is a Philippines region associated with very poor child, infant and maternal mortality indicators (Philippines Statistic Authority, 1993-1998 compared to most other regions. Graduate tracking records from SHSPalo show that in the 27 years since the school graduated its first cohort of medical graduates (in 1985), 90% of its medical graduates continue to serve in areas of dire need in the Philippines (SHS Graduate Tracking Data, Office of the College Secretary 2012), but there is no other goodquality evidence of the actual impact of SHS-Palo graduates on the local medical workforce, and limited published evidence of the impact of socially accountable training globally (Reeve et al 2016).…”
Section: The Study Settingmentioning
confidence: 99%